Applying The Theory Of Differential Equations In Economics (Eurasian Journal of Physics,Chemistry and Mathematics, 2024)
In modern science, differential equations play an extremely important role. They have many applications in various fields, one of which is economics. It is extremely important for economics students to master this theory and be able to apply it in practice